Witnessing Capital Punishment: Vigny's Ambivalent Bystander. (2nd April 2016) - Bernthal, Sarah
Abstract : In his historical novels, Alfred de Vigny links questions of free will and political agency to spectacles of public execution. His fiction places witnesses of death in predicaments where time seems to slow as they experience the longing to take action alongside the constraint of being caught up in the course of events, history, and normative behaviour. Despite the near impossibility of saving the condemned, executions tempt Vigny's protagonists to interfere. When they fail to take timely action, they experience the helplessness of vicarious death. Vigny's scenes of capital punishment highlight contradictions in the author's philosophy of political disengagement while creating thought experiments that address the ethical and epistemological stakes of watching others die. I argue that Vigny reshaped arguments against the death penalty by interrogating human capacity for free will, knowledge, and action.